Pengaruh Hydrogel Acemannan dengan Konsentrasi 25%, 50%, 75% terhadap Jumlah Neutrofil pada Tikus Wistar Periodontitis yang Diinduksi Aloksan - Chandra Susanto; Cindy Denhara Wijaya; Gebriela Lam Ulina Putri Turnip (Jurnal Penelitian Pendidikan IPA, 2024)
Neutrophils occur in periodontitis, an infection of the periodontal tissue that may increase the risk of diabetes. Because of its excellent physicochemical properties and biological capabilities, hydrogel is a promising biomaterial for treating periodontal disease. This study consisted of four groups of Acemannan hydrogel 25%, 50%, 75%, and the Federer formula was used to determine the sample size and six replicate experiments were performed for each group to form a positive control group. Considering the investigation's conclusions, in the acemannan hydrogel administration group, the average ± SD levels of neutrophils in samples on day 3 were 25%, 50%, and 75%, and the positive control group was 3.08 ± 0.736. 2.46 ± 0.459; 1.54 ± 0.510; 1.17 ± 0.258. This value decreased to 1.83 ± 0.258 by day 5 were 1.29 ± 0.459; 0.50±0.447; 0.21 ± 0.292. As a result of the Kruskal-Wallis statistical test, there was a significant difference in the average number of neutrophils after administering 25%, 50%, and 75% Acemannan hydrogel and the positive control group to rats with alloxan-induced Wistar periodontitis on the third and fifth days. The study's findings suggest that 75% of acemannan hydrogel is the most effective concentration for reducing neutrophils